LATIN AND ANCIENT GREEK MYTHOLOGY ABOUT MEDICINE AND HEALERS (Literature review) - Uktam D. Esanov,; Abdunazar Kh. Juraev,; Barno R Rajabova, (Central Asian Journal of Medicine, 2023)
As it is well known that medical terminology is based on Latin and Greek terminology. This article describes some explanation about how mythology and God as Asclepius and religion affects to the appearance of medicine according to some literature review. While reading the article reader will understand that Asclepius was the founder of family medical school and will know the most revered children of the asclepian God were: Hygieia - goddess of Health from this name comes modern terminology –Hygiene, all - round healing Panacea - patron of medicinal healing (Greek Panacea-cure for all diseases), Machaon, became a famous military surgeon, and Podalirius is famous for treating internal diseases. As well as it is interesting to reader the appearance of the snake as a symbol of medicine for all over the world.